Emergence of Novel Patterns in Dried Droplets of Combinations of Low Potencies of Plant Extracts and Salts Compared to Single Substances: A Pilot Study - Fahrentrapp, Johannes; Baumgartner, Stephan; Würtenberger, Sandra; Doesburg, Paul; Kokornaczyk, Maria Olga (Homeopathy, 2025)
Background Patterns in dried droplets have previously facilitated the characterization of homeopathic preparations of different substances at low potency levels. The objective of the present study was to examine combinations of plant extracts and salts in 2x and 3x potency (nominal dilution of 10−2 and 10−3) and to determine which influence the plant and salt components have on the patterns of these mixtures.Methods We used the droplet evaporation method (DEM) to test seven plant extracts, five salt solutions and their 1:1 combinations, either in 2x or 3x potency levels. Drops of each sample were evaporated and the resulting patterns were photographed with a dark-field microscope at 25-fold and 100-fold magnification. The images were analyzed mainly visually for their characteristics; a supporting quantitative analysis was performed by means of the computer program ImageJ for several textural features.Results Patterns of 2x potencies showed more and richer structures than those of 3x potencies. At both tested potency levels, patterns of plant–salt potency combinations exhibited structures that were different from those of single potencies.Conclusion Combining homeopathic potencies led to the emergence of novel patterns differing from those formed by the single components. There were noticeable differences in the extent to which specific salts appeared to retain their characteristic patterns in relation to the plant potency with which they were combined. This pilot study has identified promising potential for the further investigation of homeopathic preparations in low dilution ranges by means of DEM, with the aim to understand better the diverse pattern-forming processes that take place in combined compared with single potency droplets. Such endeavor would help to address the current lack of fundamental research on potency combinations.
Keywords: droplet evaporation method; pattern formation; combination remedies; basic research; low dilution range